ANALYZING THE IMPACT OF SOCIAL CLASS ROLE TOWARDS WOMEN’S CAREER (STUDY CASE ON EMPLOYEE OF BANK OCBC NISP BRANCH MANADO AND BANK BNI REGIONAL OFFICE BRANCH MANADO) - Sundah, Prisilia Ester; Pangemanan, Sifrid S.; Worang, Frederik G. (Universitas Sam Ratulangi, 2019)
Abstract: Social status and class system exist within every country of the world, in social life, we can see that there is a differentiation prevailing in social life. The purpose of this study is to analysis the Impact of Social Class Role towards Women's Career with a case study on employees at Bank OCBC NISP Branch Manado and Bank BNI regional Office Branch Manado. This research is using qualitative research method that explores the theories from several journal, articles, book and previous research. This research uses an exploratory approach with in-depth interviews to collect data from ten informants. Respondents were chosen by purposive sampling. The results indicate that their feel it is their pride to be career women who have achievements with the social class they have. Starting from be proud of career achievements, proud of achievements in social class position of the strata, and pride in the level of education, experience, work achievements. It can make them feel more Respected and more Appreciated in lives of their career. It also can bring a motivation in social life and career life that is to be a motivation to get a better career (position). Researcher recommend for all the women’s career by having a social class, employees must be more responsible. Therefore, must pay more attention to attitudes and behavior and maintain the good name of the company. Keywords: social class, social status, women, career, role of social class, women’s career